The Semantics of Japanese Postpositions and Indonesian Prepositions: A Contrastive Analysis - Andyrestu, Aryoga; Widodo, Pratomo (Makassar State University, 2024)
Abstract. Adpositions are an important aspect in Japanese language learning aspect which must mastered since the beginner level. However, despite its importance, many learners struggle to fully comprehend the meaning and semantics of each adposition. This study seeks to contrast of each semantic of the Japanese postpositions 'ni' and 'de' and Indonesian preposition 'di' stated in Japanese dictionary and Indonesian textbook, and suggestions for Japanese language learners from Indonesian for reducing errors in the use of Japanese postpositions 'ni' and 'de' based on I-JAS Corpus data. The descriptive method was utilized, with contrastive analysis serving as the chosen data analysis technique. The implementation procedures were as follows: (1) collecting data from books and dictionaries; (2) analysing the data so that similarities and differences between adpositions in Japanese and Indonesian can be contrasted in terms of semantics; (3) collecting data on errors in the use of Japanese postpositions from Indonesian students in I-JAS corpus data; and (4) analysing the corpus data, namely explaining the reasons and types of errors and proposing suggestions so that Indonesian learners can reduce these errors in their Japanese language learning. The findings revealed that there are 23 semantics of Japanese postposition ‘ni’ and ‘de’ and Indonesian preposition ‘di’, where the Japanese postposition ‘ni’ has 11 semantics, the Japanese postposition ‘de’ has 12 semantics, and the Indonesian preposition ‘di’ has 3 semantics which are the same as the Japanese postpositions ‘ni’ and ‘de’ and becomes the 3 points of the similarities and differences between the postpositions 'ni' and 'de' in Japanese and the preposition 'di' in Indonesian, and there are three types of errors of using Japanese postpositions 'ni' and 'de' based on I-JAS Corpus data; (a) The errors of using Japanese postposition 'ni', (b) The errors of using Japanese postposition 'de', (c) The errors of using Japanese particle or postposition which should be 'ni' or 'de'. The outcomes of this study hold potential as valuable reference material for translators and Japanese instructors involved in teaching Japanese particles or postpositions. By utilizing this resource, the distinctions among these postpositions can be explained more clearly also it offers comprehension for both translators and Japanese language learners in Indonesia.Keywords: Semantic, Contrastive, Corpus, Japanese Postpositions, Indonesian Prepositions